Diet, Home range and habitat use effects on the seed dispersal of a pioneer tree by two Bulbul species - Thanate Kerdkaew (Prince of Songkla University, 2014)
Thesis (M.Sc.(Ecology, International Program))--Prince of Songkla University, 2014